Privacy Online: New Forms of Domestic Violence in the Age of Digital Surveillance - Stepanović, Ivana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
Digital surveillance is ubiquitous and uses various intrusive technologies which pose a threat to privacy. From built-in cameras that capture images and videos to sensors, GPS systems, and massive databases, these new technologies are incorporated into everyday life and are exposing the private zone in new and unexpected ways. As a result, new forms of domestic violence start to emerge. This paper is investigating the impact and implications these new forms of domestic violence have on the concept of privacy. It seems that these new technologies are radically redefining privacy, considering the fact that domestic violence is being exported from the privacy of the home into the public domain of the internet. Furthermore, it can be argued that various contradictory definitions of privacy are being used to create strategies to either justify violence or protect victims, which is why the concept is further relativised and devalued.